Structural and Energetic Properties of HCN-BCl[subscript]3 and HCN-BBr[subscript]3 via Computations - Danforth, Samuel J.; Bloomgren, Kaitlin M. (My University, 2013)
The purpose of this study was to examine the effects of condensed-phase environments on the structural properties of nitrile-BCl[subscript]3 complexes.
Color poster with text, charts, tables, and graphs.
Keywords: Condensed-phase environment; Nitriles; Posters